Protection against Influenza Virus Infection of Mice Fed Bifidobacterium breve YIT4064 - Yasui, Hisako (American Society for Microbiology (ASM), 1999)
Mice fed Bifidobacterium breve YIT4064 and immunized orally with influenza virus were more strongly protected against influenza virus infection of the lower respiratory tract than ones immunized with influenza virus only. The number of mice with enhanced anti-influenza virus immunoglobulin G (IgG) in serum upon oral administration of B. breve YIT4064 and oral immunization with influenza virus was significantly greater than that upon oral immunization with influenza virus only. These findings demonstrated that the oral administration of B. breve YIT4064 increased anti-influenza virus IgG antibodies in serum and protected against influenza virus infection. The oral administration of B. breve YIT4064 may enhance antigen-specific IgG against various pathogenic antigens taken orally and induce protection against various virus infections.